2017
DOI: 10.1002/lsm.22674
|View full text |Cite
|
Sign up to set email alerts
|

Multiple same day cryolipolysis treatments for the reduction of subcutaneous fat are safe and do not affect serum lipid levels or liver function tests

Abstract: ObjectiveCryolipolysis is a safe and effective non‐surgical procedure for reducing subcutaneous fat. It spares adjacent structures, is associated with few adverse events, and is well‐tolerated by patients. Previous studies involving one or two simultaneous treatment sites have shown no effect on serum lipid levels or liver tests. The purpose of this study was to determine whether multiple same day treatments (abdomen plus both flanks) result in changes in these blood tests, and is safe.Study DesignThirty‐five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 11 publications
0
45
1
Order By: Relevance
“…Cryolipolysis has been studied extensively for its safety and efficacy to reduce nonfacial focal lipodystrophy . There have been no changes in lipid levels or liver function tests and no peripheral nerve damage . A systemic literature review evaluating the safety and efficacy of cryolipolysis for body contouring showed that only 0.82% reported adverse effects last greater than 4 weeks, with decreased sensation being most common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cryolipolysis has been studied extensively for its safety and efficacy to reduce nonfacial focal lipodystrophy . There have been no changes in lipid levels or liver function tests and no peripheral nerve damage . A systemic literature review evaluating the safety and efficacy of cryolipolysis for body contouring showed that only 0.82% reported adverse effects last greater than 4 weeks, with decreased sensation being most common.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether rapid lysis of adipocytes would lead to fluctuations in lipids or liver damage, two clinical trials were performed on patients undergoing cryolipolysis to their lower abdomen and flanks . In the first trial, 40 subjects were treated with a cooling device to their bilateral flanks and blood tests were performed prior to treatment and on post‐treatments day 1, and then 1, 4, 8, and 12 weeks after treatment .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used cryolipolysis device, Coolsculpt ® (ZELTIQ Aesthetics, Inc., Pleasanton, CA, USA), first received FDA clearance for fat reduction in the flank area in 2010. Since this time, cryolipolysis has been approved for several other body areas, including the abdomen, flank, thighs, buttocks, submental area, bra fat, back fat and, less commonly, the upper arms …”
Section: Cryolipolysis Body Sculptingmentioning
confidence: 99%
“…Cryolipolysis is based upon the greater susceptibility of lipid-rich adipocytes to cold injury compared to surrounding water-rich cells [1][2][3]. Numerous clinical studies have demonstrated the safety, efficacy, and tolerability of cryolipolysis in multiple areas [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%